Quercetin Attenuates Podocyte Apoptosis of Diabetic Nephropathy Through Targeting EGFR Signaling - Liu, Yiqi; Li, Yuan; Xu, Liu; Shi, Jiasen; Yu, Xiujuan; Wang, Xue; Li, Xizhi; Jiang, Hong; Yang, Tingting; Yin, Xiaoxing; Du, Lei; Lu, Qian (Frontiers in Pharmacology, 2022)
Podocytes injury is one of the leading causes of proteinuria in patients with diabetic nephropathy (DN), and is accompanied by podocytes apoptosis and the reduction of podocyte markers such as synaptopodin and nephrin. Therefore, attenuation of podocyte apoptosis is considered as an effective strategy to prevent the proteinuria in DN. In this study, we evaluated the anti-podocyte-apoptosis effect of quercetin which is a flavonol compound possessing an important role in prevention and treatment of DN and verified the effect by using db/db mice and high glucose (HG)-induced mouse podocytes (MPs). The results show that administration of quercetin attenuated the level of podocyte apoptosis by decreasing the expression of pro-apoptotic protein Bax, cleaving caspase 3 and increasing the expression of anti-apoptotic protein Bcl-2 in the db/db mice and HG-induced MPs. Furthermore, epidermal growth factor receptor (EGFR) was predicted to be the potential physiological target of quercetin by network pharmacology. In vitro and vivo experiments confirmed that quercetin inhibited activation of the EGFR signaling pathway by decreasing phosphorylation of EGFR and ERK1/2. Taken together, this study demonstrates that quercetin attenuated podocyte apoptosis through inhibiting EGFR signaling pathway, which provided a novel approach for further research of the mechanism of quercetin in the treatment of DN.